Functional complementation of a conserved non protein-coding element (CNE) of Autographa californica multiple nucleopolyhedrovirus by heterologous CNE originating from Malacosoma neustria nucleopolyhedrovirus - Kikhno, I.M.; Makarenko, V.E.; Kashuba, V.I. (Вiopolymers and Cell, 2016)
Aim. To assess the functional conservation of a baculovirus CNE. Methods. CNE deletion from the baculovirus genome and its replacement with a heterologous CNE was performed by using the bacmid-based technology. Transfection-infection assays were used to investigate cell-to-cell spread of the recombinant virus. Results. The recombinant Autographa californica multiple nucleopolyhedrovirus genome carrying the Malacosoma neustria nuclepolyhedrovirus CNE in place of the innate CNE was constructed. The recombinant virus was able to transmit the infection in a cell culture. Conclusions . The CNE essential function was foundto be conserved between the representatives of I and II groups of the genus Alphabaculovirus. Мета. Оцінити функціональну консервативність бакуловірусного CNE (conserved non protein-coding element). Вивчити функціональне заміщення консервативного некодуючого елемента (CNE) вірусу ядерного поліедроза Autographa californica на СNE вірусу ядерного поліедрозу Malacosoma neustria. Методи. Видалення CNE з вірусного генома і його заміщення гетерологічним CNE було виконано з використанням бакмідной технології. Трансфекційно-інфекційний аналіз був застосований для дослідження поширення рекомбінантного вірусу від клітини до клітини. Результати. Було сконструйовано рекомбінантний геном віруса ядерного поліедрозу Autographa californica, що несе в своєму складі CNE віруса ядерного поліедрозу Malacosoma neustria замість власного CNE. Показано, що рекомбінантний вірус здатний передавати інфекцію в культурі клітин. Висновки. Абсолютно обов’язкова функкція CNE є консервативною для представників I і II груп роду Alphabaculovirus. Цель. Оценить функциональную консервативность бакуловирусного CNE (conserved non protein-coding element). Методы. Удаление CNE из вирусного генома и его замещение гетерологичным CNE было выполнено с использованием бакмидной технологии. Трансфекционно-инфекционный анализ был применен для изучения распространения рекомбинантного вируса от клетки к клетке. Результаты. Был сконструирован рекомбинантный геном вируса ядерного полиэдроза Autographa californica, несущий в своем составе CNE вируса ядерного полиэдроза Malacosoma neustria вместо собственного CNE. Было показано, что рекомбинантный вирус способен передавать инфекцию в культуре клеток. Выводы. Абсолютно обязательная функция CNE является консервативной для представителей I и II групп рода Alphabaculovirus.